Prader-Willi syndrome in siblings, due to unbalanced translocation between chromosomes 15 and 22. Issue 8 (August 1987) - Fernandez, F; Berry, C; Mutton, D
Abstract : In a family in which the father carried a balanced translocation between chromosomes 15 and 22 two of his children had Prader-Willi syndrome and an unbalanced chromosome complement, having lost the proximal bands from the long arm of chromosome 15. His four other surviving children were normal but carried a balanced translocation.